Veterinary Students’ Knowledge of Thyroid Hormones and Educational Needs: Pengetahuan Mahasiswa Kedokteran Hewan tentang Hormon Tiroid dan Kebutuhan Pendidikan - Wathiq Faraon Hussein (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The thyroid gland, an essential endocrine organ located in the anterior neck, regulates iodine homeostasis and secretes thyroid hormones that influence metabolism and cellular function. Specific Background: Understanding thyroid hormone physiology is crucial for veterinary students, as it impacts both human and animal health. Knowledge Gap: Limited research exists on veterinary students’ awareness of thyroid hormone physiology, particularly its effects on the body. Aims: This study assesses veterinary students’ knowledge of thyroid hormone function and provides recommendations to enhance their understanding. Methodology: A descriptive, cross-sectional, questionnaire-based study was conducted at the College of Veterinary Medicine, University of Basrah, with 150 students (86 females, 64 males). The questionnaire included demographic data and knowledge assessments on thyroid function, hypothyroidism, and hyperthyroidism. Results: Female students constituted the majority (57.33%). Most participants (94%) were aged 19–28. The results showed varying levels of knowledge, with 95% of responses being significant and a high mean score, indicating substantial understanding of thyroid hormone effects. Novelty: This study highlights veterinary students' competence in endocrinology and suggests targeted educational interventions for knowledge enhancement. Implications: Findings emphasize the need for improved curriculum design and interactive learning strategies to reinforce thyroid physiology education in veterinary programs. Highlights: Knowledge Levels: Students showed varied understanding of thyroid hormone function. Significant Findings: 95% of responses were significant, indicating strong knowledge. Educational Implications: Findings highlight the need for better thyroid education. Keywords: Thyroid gland, Veterinary students, Endocrinology, Hormone physiology, Knowledge assessment